Influence of risk-organ–based tube current modulation on CT-induced DNA double-strand breaks in a biological phantom model. (20th September 2018) - Brand, Michael; Wuest, Wolfgang; May, Matthias; Uder, Michael; Sommer, Matthias
Abstract: Techniques for dose reduction in computed tomography (CT) are receiving increasing attention. Lowering the tube current in front of the patient, known as risk-organ–based tube current modulation (RTM), represents a new approach. Physical dose parameters can determine the exposure but are not able to assess the biological–X-ray interactions. The purpose of this study was to establish a biological phantom model to evaluate the effect of RTM on X-ray–induced DNA double-strand breaks (DSBs). In breast phantoms and in the location of the spine in an Alderson phantom, isolated human blood lymphocytes were irradiated using a 128-slice CT scanner. A standard thoracic CT protocol (120 kV, 110 ref. mAs, anatomy-based tube current modulation, pitch 0.6, scan length 30 cm) with and without RTM was used. X-ray–induced DSBs were quantified in isolated blood lymphocytes using immunofluorescence microscopy after staining for the phosphorylated histone variant γ-H2AX. Using RTM, the resulting DNA damage reduction was 41% in superficial breast locations ( P = 0.0001), 28% in middle breast locations ( P = 0.0003) and 29% in lower breast locations ( P = 0.0001), but we found a DNA damage increase of 36% in superficial spine locations ( P = 0.0001) and of 26% in deep spine locations ( P = 0.0001). In summary, we established a biological phantom model that is suitable for detecting DNA damage in distinct organs. In addition, we were able to show that, using RTM, X-ray–induced DNA damage in the breast can be significantly reduced; however, there is a significant increase in DSBs in the location of the spine.